Citizens of a Stolen Land : A Ho-Chunk History of the Nineteenth-Century United States - Kantrowitz, Stephen David, 1965- (Book collections on Project MUSE., 2023)
"In this book, Steven Kantrowitz explores the transformations of American citizenship in the Civil War era through the history of the Ho-Chunk people. Kantrowitz has had opportunity to work closely with members of the Ho-Chunk tribe, whose home territory centers around Madison, and this work grows out of his interest in their particular struggles for citizenship and recognition"--